Long Term Impacts of One Off Grants to Microenterprises - Mel, Suresh de; McKenzie, David; Woodruff, Christopher (World Bank, Washington, DC, 2012)
Traditional economic models of investment such as the Ramsey model would predict that such grants should have at most temporary effects. In such models, there is an efficient steady state size for a business conditional on the ability of the owner. A positive shock to capital in such a model will have only temporary effects, speeding up convergence to this steady state, but those firms that did not receive the grants should be able to catch up over time by taking advantage of the high returns to capital and reinvesting in their business. The results highlight that a one-off grant can have a lasting impact on some types of microenterprises. This has implications both for charitable giving, and for policymakers deciding which types of microenterprises to target for assistance.